The Halo Vest Immobilization for Craniocervical Junction Tuberculosis: A Comparison of Treatment Options - Yunfeng Wu; Xiyou Yang; Long Yu; Ning Liu; Shangjie Yang; Xu Cui (Orthopaedic Surgery)
ABSTRACT Objective The treatment of tuberculosis at the craniovertebral junction (CVJ) remains challenging, with significant debate surrounding therapeutic approaches. Halo vest (HV) therapy provides a non‐invasive immobilization alternative, while occipitocervical fusion (OCF) offers a surgical option. However, limited evidence exists comparing the efficacy of HV therapy with OCF for CVJ tuberculosis. This study aimed to evaluate the clinical outcomes and safety of HV immobilization in treating CVJ tuberculosis, compared with OCF. Methods This retrospective cohort study was conducted from January 2012 to December 2022 and included 43 patients diagnosed with CVJ tuberculosis. Radiographic and treatment data were meticulously analyzed to compare outcomes between patients treated with HV immobilization (Group H, n = 22) and those undergoing OCF (Group O, n = 21). Interventions comprised at least 28 weeks of HV immobilization for Group H and OCF supplemented with postoperative external fixation for Group O. Outcomes were evaluated using the Visual Analog Scale (VAS‐neck), erythrocyte sedimentation rate (ESR), and radiographic stability (assessed via X‐ray and CT). Statistical analyses included the Student's t‐test (parametric data), Mann–Whitney U test (nonparametric data), and chi‐square test (categorical variables), with a significance level set at p < 0.05. Results Over a 24‐month follow‐up, all patients exhibited successful healing of tuberculosis lesions. Group H demonstrated greater improvements in cervical flexion‐extension and rotation function compared with Group O. Both groups showed statistically significant decreases in Visual Analog Scale (VAS‐neck) and Neck Disability Index (NDI) scores, as well as in ESR and C‐reactive protein (CRP) values from pre‐surgery levels (p < 0.01). Notably, differences in VAS‐neck (1 month) and NDI (24 months) between the groups were statistically significant (p < 0.05), while no significant differences were observed in other follow‐up periods (p > 0.05). Additionally, there were no significant differences in ESR and CRP values at any time point between the treatment groups (p > 0.05). Conclusions The study yielded satisfactory outcomes for all patients. Short‐term differences in pain relief did not significantly impact the healing of CVJ tuberculosis. Patients receiving HV treatment showed greater improvement in neck function compared with those undergoing occipitocervical fusion. Given the substantial costs and risks associated with open surgery, we advocate for conservative treatment utilizing HV.